Enhancing Fundraising with Digital Transaction in Indonesia: A Systematic Literature Review (SLR) - Safitri, Devi Herlinda; Dzikrulloh, Dzikrulloh (Perisai : Islamic Banking and Finance Journal, 2024)
This research uses the Systematic Literature Review (SLR) method to investigate the optimization of collecting Zakat, Infaq and Sadaqah funds through digital transactions. The data analysis process uses the PRISMA diagram and includes the stages of identification, search, selection, data collection and analysis. From three main sources, researchers collected 20 references, consisting of theses and journals, which were analyzed to identify findings related to collecting ZIS funds with digital transactions in Indonesia. The results reflect the digitalization trend, where zakat institutions are increasingly using information technology to increase efficiency, accessibility and transparency in the process of collecting ZIS funds. This trend involves utilizing mobile applications, QRIS, and digital platforms, enabling faster and more efficient fund collection. Other benefits include ease of access, increased transparency, and more effective involvement of muzakki. Using digital technology also enables data analysis, better fund management and the development of sustainable business models. The COVID-19 pandemic has triggered new strategies in collecting ZIS funds, with zakat institutions turning to social media and digital platforms as alternatives to raise funds. Online payment services with mobile QR Codes are key in maintaining the continuity of ZIS fund collection amidst physical restrictions. Socialization efforts, easy access, and partnerships with various parties are the main strategies for zakat institutions to remain relevant and effective in facing the challenges of the pandemic. This research focuses on the central role of digitalization in increasing the efficiency and effectiveness of collecting ZIS funds, such as paying attention to social changes, namely the COVID-19 pandemic. By using digital technology, zakat institutions can continue to innovate and meet the needs of muzakki, so that they continue to play their role in helping people in need.